Processing and characterization of the low density lipoprotein receptor in the human colonic carcinoma cell subclone HT29-18: A potential pathway for delivering therapeutic drugs and genes. Issue 6 (December 1992) - Mazière, J. C.; Mazière, C.; Emami, S.; Noel, B.; Poumay, Y.; Ronveaux, M. F.; Chastre, E.; Porte, H.; Barbu, V.; Biade, S.; Santus, R.; Gespach, C.
Abstract : Low density lipoprotein (LDL) processing has been investigated in the subcloned human colonic carcinoma cell line HT29-18. LDL binding at 4°C was a saturable process in relation to time and LDL concentration. The Kd for LDL binding was 11 μg/ml. ApoE-free HDL3 or acetylated LDL did not significantly compete with 125 I-LDL binding, up to 500 μg/ml. 125 I-LDL binding was decreased by 70% in HT29-18 cells preincubated for 24 hours in culture medium containing 100 μg/ml unlabelled LDL. Ligand blotting studies performed on HT29-18 homogenates using colloidal gold labelled LDL indicated the presence of one autoradiographic band corresponding to an apparent molecular weight of 130 kDa, which is consistent with the previously reported molecular weight of the LDL receptor in human fibroblasts. At 37°C, 125 I-LDL was actively internalized by HT29-18 cells and lysosomal degradation occurred as demonstrated by the inhibitory effect of chloroquine. LDL uptake and degradation by HT29-18 cells also resulted in a marked decrease in endogenous sterol synthesis. These data demonstrate that the HT29-18 human cancerous intestinal cells are able to specifically bind and internalize LDL, and that LDL processing results in down-regulation of sterol biosynthesis. Thus, intestinal epithelial cells possess specific LDL receptors that can be exploited to accomplish drug delivery and gene transfer via the receptor-mediated endocytosis pathway.